Shallow S-wave Velocity Profile Estimation using Surface Velocity and Microtremor HVSR with a Linear Velocity Increase Approach - Andi Muhamad Pramatadie; Hiroaki Yamanaka; Afnimar Afnimar (Journal of Mathematical and Fundamental Sciences, 2023)
We propose a simple method for 1D S-wave velocity (Vs) profile estimation using a measured surface S-wave velocity (V1) and peak frequency of the observed microtremor horizontal-to-vertical spectral ratio (HVSR). In this method, the S-wave velocity profile is presented as linear velocity increase with depth in sediments over a bedrock layer that has a given constant S-wave velocity. Thus, the profile can be parameterized with the measured surface S-wave velocity and the velocity gradient. The gradient can be estimated based on the agreement of the peak frequencies of the observed microtremor HVSR and the theoretical ellipticity of the fundamental mode of the Rayleigh wave. We examined the applicability of the proposed method using numerical tests as well as application to actual data at five sites in the Bandung Basin, Indonesia, where observed Rayleigh wave phase velocities from microtremor array surveys were available. The applicability was confirmed in numerical tests using sample models of soil profiles in the basin. Actual application indicated the appropriateness of the estimated S-wave velocity profiles due to the similarity of their theoretical Rayleigh wave phase velocities with the observed Rayleigh wave phase velocities. Since the proposed method needs prior confirmation of the linear increase of the S-wave velocity, it is suitable for use in spatial interpolation of shallow S-wave velocity profiles with simple data acquisition.